2019
DOI: 10.1002/ange.201900466
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyzed Cyanodifluoromethylation of Alkenes

Abstract: Difluoromethylation is astraightforwardand widely applied strategy used to incorporate HCF 2 into organic molecules.Incontrast, cyanation reagents are typically volatile or highly toxic,o rt hey require harsh reaction conditions. Incorporation of both CN and HCF 2 into organic molecules, such as alkenes,isaworthwhile but challenging task. Amethod for photocatalyzed cyanodifluoromethylationo fa lkenes has been developed, which employs aP h 3 P + CF 2 CO 2 À /NaNH 2 (or NH 3 )r eagent system. Ph 3 P + CF 2 CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…26 The cyano substrate (2a) on treatment with NaN 3 is transformed to a tetrazole moiety (2e) without affecting the oxime functionality. 27 In conclusion, a visible-light-mediated synthesis of Nhydroxybenzimidoyl cyanides have been accomplished from styrenes in the presence of organic photoredox catalyst. The bifunctionalized moiety possesses two important functionalities, viz, an oxime and a nitrile group, which originate from tert-butyl nitrite and ammonium acetate, respectively.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…26 The cyano substrate (2a) on treatment with NaN 3 is transformed to a tetrazole moiety (2e) without affecting the oxime functionality. 27 In conclusion, a visible-light-mediated synthesis of Nhydroxybenzimidoyl cyanides have been accomplished from styrenes in the presence of organic photoredox catalyst. The bifunctionalized moiety possesses two important functionalities, viz, an oxime and a nitrile group, which originate from tert-butyl nitrite and ammonium acetate, respectively.…”
mentioning
confidence: 93%
“…Furthermore, the treatment of ( 2a ) with a phenylboronic acid in the presence of Pd­(II) catalyst, both the oxime and cyano functionality were converted to keto group ( 2d ) with concurrent incorporation of a phenyl group . The cyano substrate ( 2a ) on treatment with NaN 3 is transformed to a tetrazole moiety ( 2e ) without affecting the oxime functionality …”
mentioning
confidence: 99%
“…Our previous work showed that the difluoromethylphosphonium salt (Ph 3 P + CF 2 H X − ) is easy to reduce by photocatalysis to realize the difunctionalization of olefins. 14 The redox potential of TFSP (E p red = −0.830 V vs SCE; see the SI) measured by cyclic voltammetry showed that it may have similar photoredox properties as Ph 3 P + CF 2 H X − . Then, we investigated the photocatalyzed azido-trifluoromethylation of TFSP with alkenes.…”
mentioning
confidence: 99%
“…Over the past few decades, many difluoromethylation reactions have been successfully developed, enabling facile synthesis of different types of difluoromethylated compounds. Most commonly, the CF 2 H group (or CF 2 R group) is accessed from a CF 2containing building block or agent [14][15][16][17][18][19][25][26][27][28][29][30][31] . For example, the syntheses of difluoromethylated allenes typically require the use of difluoromethyl metal compounds [32][33][34][35] .…”
mentioning
confidence: 99%